Afirmação cultural: (re) construindo a Casa da Cultura de Parintins - Oliveira, Milena Rocha de (Brasil, 2024)
The proposed theme simulates a project for the renovation and requalification of the Parintins Cultural Center and its surroundings, located in the municipality of Parintins in the state of Amazonas, northern region of Brazil. Through an in-depth case study, it seeks to understand the causes of its current state of deterioration and meet the deficits of cultural support that the national capital of Boi Bumbá still has with the requalification of the surroundings, in order to promote pleasant urban spaces for the population. The project will be developed through a theoretical framework on the history of the Cultural Center, analysis of documentary projects and original plans. In addition, an analysis of the urban and architectural context in which the building is inserted will be carried out, considering aspects such as the relationship with the surroundings, accessibility, and infrastructure. Considering the research results, a requalification project for the Cultural Center and its surroundings will be proposed, aiming at its physical and functional recovery, as well as its reinsertion into the urban fabric. The project must consider the key points for Architecture in the Amazon as a main guideline, as well as reaffirm the popular culture existing in Parintins, strengthening the community's sense of belonging.